The Dilemma of Community Using Medicine and the Performance of BPOM in Medan - Roswita Sitompul (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Medicine is something that is very important in human life because humans are not always healthy, medicine is something that is consumed by consumers so that human medicine can be healthy and can return to activity because it must be remembered that a body that is physically and mentally healthy can contribute to the State, society and family. This research is a descriptive and empirical normative, where the data collection is carried out by observation, interviews, the results of which are assessed qualitatively and quantitatively so that it can provide an idea of how the actual application of protection to consumers who consume contaminated drugs that can trigger cancer. It turns out that even though there is Law No. 8 of 1999 on Consumer Protection.